Prefreezing application of whey protein-based edible coating to maintain quality attributes of strawberries - Soazo, Marina del Valle (2015)
Prefreezing application of whey protein concentrate (WPC)-based edible coating to maintain quality attributes of strawberries was studied. Beeswax (BW) was added to the solutions (0%, 20% and 40% with respect to the solids contained in the mixture WPC/glycerol). Coated and control fruits were frozen, stored at −20 °C and thawed. After thawing, weight loss, firmness, microstructure and colour parameters were measured. Coating with 20% BW reduced strawberries weight loss after thawing (55%). Strawberries firmness was maintained equally in all groups analysed although a slight improvement at the cell microstructure alterations caused by the freezing process was observed in coated fruits. Strawberries brightness was similar in all groups. Colour parameter a* showed a tendency to decrease with the increasing BW concentration, and only b* of coated fruits was lower than controls. The application of whey protein coating could be an attractive treatment to maintain quality attributes of strawberries undergoing the freezing process.